2008
DOI: 10.1557/mrs2008.220
|View full text |Cite
|
Sign up to set email alerts
|

Whither Oxide Electronics?

Abstract: In this issue we have endeavored to answer the question, "Whither oxide electronics?" This issue provides a framework and perspective on the progress in the field of oxide electronics over the past several decades, as well as the challenges and opportunities in the years to come. Building on the foundations laid by the pioneers in the materials community and spurred by the discovery of high-temperature superconductivity, there has been both tremendous progress in understanding the complex science of oxide elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
82
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(82 citation statements)
references
References 63 publications
0
82
0
Order By: Relevance
“…[1][2][3] Recent work has demonstrated that the functionality of these materials can be further expanded through the formation of superlattices, which can exhibit enhanced properties compared to bulk compounds. While the majority of work in this field has focused on the electronic and ferroic properties of oxide superlattices, 4-9 the impact of heterointerfaces on the local atomic structure has received less attention.…”
mentioning
confidence: 99%
“…[1][2][3] Recent work has demonstrated that the functionality of these materials can be further expanded through the formation of superlattices, which can exhibit enhanced properties compared to bulk compounds. While the majority of work in this field has focused on the electronic and ferroic properties of oxide superlattices, 4-9 the impact of heterointerfaces on the local atomic structure has received less attention.…”
mentioning
confidence: 99%
“…4 Domain formation in ferroelectrics has been largely studied. 2,3,[5][6][7][8][9][10][11][12][13][14][15] In order to adapt to the substrate and to locally minimize the mismatch strain or the depolarizing field, the domains form in a periodic manner. 6,7 It is known that there is a quadratic dependence, W / d 1=2 , of the domain width (W) with the crystal thickness (b).…”
mentioning
confidence: 99%
“…From this perspective, epitaxial thin films are of particular interest due to their characteristics and performances. 1,2 For ferroelectric/ piezoelectric materials, examples of applications that will benefit from this achievement are ferroelectric random access memories, surface acoustic wave devices, and piezoelectric-driven microelectromechanical systems ͑piezo-MEMS͒.…”
mentioning
confidence: 99%